Clinical Evaluation of Preoperative Radiotherapy Combined with FOLFOX Chemotherapy on Patients with Locally Advanced Colon Cancer. Issue 4 (April 2019) - Zhou, Jing; Guo, Zuoming; Yu, Weiqiang; Li, Shan; Qiao, Wenbo
This study explores the effect of preoperative radiotherapy combined with FOLFOX chemotherapy on patients with locally advanced colon cancer (LACC). Data of 102 patients with LACC were retrospectively analyzed. All received surgical resection plus postoperative FOLFOX chemotherapy; whereas 58 patients underwent preoperative radiotherapy combined with FOLFOX chemotherapy (CRT group, combined with radiotherapy treatment group), 44 patients did not undergo radiotherapy (non-CRT group). Short-and long-term effects as well as operative complications were compared. The optical density values of the caudal-related homeobox transcription factor 2 and inhibitor of growth 4 in lesions, and malignant molecules including vascular endothelial growth factor and cathepsin-D in serum were compared. The CRT group showed higher total pathological complete tumor response rate and resection rate, and lower incidence of incisional infection than the non-CRT group (all P < 0.05). The CRT group was significantly better in the three-year disease-free survival than the non-CRT group ( P < 0.05), but slightly better in the three-year overall survival and disease-free survival in the first, second, and third years ( P > 0.05). The optical density values of the caudal-related homeobox transcription factor 2 and inhibitor of growth 4 were higher than those in the non-CRT group (both P < 0.05). The levels of serum vascular endothelial growth factor and cathepsin-D in the CRT group were lower than those in the non-CRT group (both P < 0.05). Preoperative radiotherapy combined with FOLFOX chemotherapy can improve the resection rate and the pathological complete response rate in LACC surgery, and improve the survival time and the disease-free survival condition.